Cardiac calcified amorphous tumor with mitral valve perforation: A case report. Issue 5 (May 2022) - Yamana, Fumio; Domae, Keitaro; Shirakawa, Yukitoshi; Masai, Takafumi
Abstract: Cardiac calcified amorphous tumors are rare non-neoplastic intracavitary masses. Herein, we report a case of a 75-year-old woman who presented with dyspnea on exertion and multiple cerebral infarctions 3 months prior. Transthoracic echocardiography showed severe mitral regurgitation from the posterior mitral leaflet with valve perforation and severe mitral annular calcification. In addition, we observed a 13 mm mobile high echogenic mass, suggesting healed infective endocarditis. The mass was successfully resected, and the mitral valve was replaced with a bovine pericardial patch for the decalcified annulus. Histopathological examination confirmed cardiac calcified amorphous tumor; the postoperative course was uneventful. Mitral valve replacement and annulus patch repair effectively prevented postoperative recurrent systemic embolization. <Learning objective: Calcified amorphous tumor (CAT) is a risk factor for systemic embolism. Cardiac CAT destroying the mitral valve tissue and causing mitral valvular disease have been scarcely reported. We present a case of cardiac CAT with mitral valve perforation and suspected systemic embolization, treated successfully through mitral valve replacement and calcified lesion coverage by surgical resection and patch repair.>